Du tourisme de masse au tourisme rural au Maroc : le cas de la commune rurale d’Asni - Taoufik Daghri; Soukaina El Omari (Études Caribéennes)
It is high people admitted that mass tourism has its limits as there have been consequences. Indeed several NGOS as well as international organizations aiming at the protection of the environment see that this destructive or harmful tourism is losing ground it is being substituted or replaced by eco-friendly tourism. This latter target the preservation of mother earth as well as its natural resources by providing a new type of tourism labeled rural tourism whose first and paramount objective is providing tourists with organic products. This green or rural tourism tries at all cost to promote artistic commodities, authentic cultures and purely traditional folk.Rural tourism is actually expecting more prosperity and progress but on condition that the local authorities and the government cooperate more to give a push to this kind of business via a perfect or division of human resources. Rural tourism represent a new image of modern tourism that aims to protect the environment and diversity. From the beauty of the natural land scape, the quality of the food served, the professionalism of the staff members the touristic accommodation units based in Moroccan countryside manage to attract a significant number of tourists, who often come for 2 or 3 days prolong their stay for a week for having fond a deep pleasure. The water is pure, the atmospheric air is filtered, the cultural wealth is vast, it is therefore appropriate to sustain and support this kind of tourism that inspires our investigation at the rural town of Asni.